Effects of System Noise and Bribery on Collective Decision Rules. - Bodo, Peter (2008)
Developed and used Monte Carlo simulation models to test the effects of system moise and bribery on collective decision rules. He wrote simulation software, ran the simulations after debugging the software, analyzed the results and wrote a research paper, and presented the paper at the annual conference of the Eastern Economic Association. The paper will be published next year.
Keywords: dept.eco; faculty_collection; sabbatical_report

Occupational Mortality, Age at Marriage and Marital Fertility in Early Twentieth Century England and Wales. - Mills, Judith Woerner (2003)
Keywords: dept.eco; faculty_collection; sabbatical_report

[Translation of 2 Books on the Financing of the French Crown in the 13th Century] - Eldridge, Robert (2001)
Keywords: dept.eco; faculty_collection; sabbatical_report

Currency Substitution in Developing Countries. - Andoh, Samuel (Spring; Economics/Finance., 2000)
Keywords: dept.eco; faculty_collection; sabbatical_report

The Development of Capital Markets and Economic Growth in Transition Economies: Sabbatical Fall 2009 - Grubacic, Sanja (2009)
This project involved gathering, analyzing, and preparing for publication the new empirical evidence on the working of capital markets in several economies of East and Central Europe, additionally providing material to enrich the curriculum in economics and finance. It also provided material for a conference presentation.
Keywords: dept.eco; faculty_collection

A lidar collaboratory data management system - Sharma, N.C.P.; Parikh, J.A.; Clark, M. (International Geoscience and Remote Sensing Symposium (IGARSS), 2006)
A data management system has been developed for the Connecticut State University (CSU) Lidar Collaboratory to facilitate user authentication, scheduling of remote lidar instrumentation control sessions, storage and retrieval of lidar datasets and generation of new data products. In addition to providing for efficient archival and retrieval of lidar data products, a major design goal of the data management system is to support collaborative, multidisciplinary, atmospheric sciences research projects. In this paper, we describe the framework of the CSU Lidar Collaboratory data management system and how the system interacts with the data acquisition and data analysis software.
3 citations (Crossref) [2023-10-31] Journal Abbreviation: Dig Int Geosci Remote Sens Symp (IGARSS)
Keywords: Atmospheric optics; Computer programming; Computer supported cooperative work; Connecticut State University (CSU); Data management systems; Data reduction; Image retrieval; Information management; Optical radar; Remote lidar instrumentation; User authentication; dept.csc

Professional sovereignty revisited: The Network Transformation of American Medicine?. - Savage, Deborah A (Journal of health politics, policy and law, 2004)
3 citations (Crossref) [2023-10-31] Place: United States Savage, Deborah A. Southern Connecticut State University, USA.
Keywords: *Hierarchy; Social; *Professional Autonomy; *Social Change/hi [History]; *Sociology; Medical/hi [History]; Education; Medical; Education; Medical/hi [History]; Health Policy; Health Policy/hi [History]; Hierarchy; Social; History; 19th Century; History; 20th Century; Humans; Politics; Power (Psychology); Power; Psychological; Professional Autonomy; Professional Corporations; Professional Corporations/hi [History]; Social Change; Sociology; Medical; Sociology; Medical/ec [Economics]; United States; dept.eco; health care organization; health care planning; health care system; health economics; history of medicine; hospital; medical decision making; medical education; medical practice; medical profession; medical society; medical technology; politics; review; social evolution; social interaction; social structure

Hedge fund crisis and financial contagion: evidence from long-term capital management - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Journal of Alternative Investments, 2005)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-096-756-230-280 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Monetary policy, composite leading economic indicators and predicting the 2001 recession - Mostaghimi, M (Journal of Forecasting, 2004)
On 26 November 2001, the National Bureau of Economic Research announced that the US economy had officially entered into a recession in March 2001. This decision was a surprise and did not end all the conflicting opinions expressed by economists. This matter was finally settled in July 2002 after a revision to the 2001 real gross domestic product showed negative growth rates for its first three quarters. A series of political and economic events in the years 2000-01 have increased the amount of uncertainty in the state of the economy, which in turn has resulted in the production of less reliable economic indicators and forecasts. This paper evaluates the performance of two very reliable methodologies for predicting a downturn in the US economy using composite leading economic indicators (CLI) for the years 2000-01. It explores the impact of the monetary policy on CLI and on the overall economy and shows how the gradualness and uncertainty of this impact on the overall economy have affected the forecasts of these methodologies. It suggests that the overexposure of the CLI to the monetary policy tools and a strong, but less effective, expansionary money policy have been the major factors in deteriorating the predictions of these methodologies. To improve these forecasts, it has explored the inclusion of the CLI diffusion index as a prior in the Bayesian methodology. Copyright (C) 2004 John Wiley Sons, Ltd.
10 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000225169500001
Keywords: Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Composite leading indicators (CLI); Composite leading indicators diffusion index; Diffusion index; Geochronology; Industrial economics; Information theory; Monetary policy; Predicting recessions; Probability; Public policy; Quality control; Set theory; Statistical methods; US economy; Us economy; dept.eco; dept.fin

Orange county bankruptcy: financial contagion in the municipal bond and bank equity markets - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Financial Review, 2004)
We examine the spillover wealth effects of the Orange County, California bankruptcy announcement in December 1994 on municipal bonds, municipal bond funds, and bank stocks. This bankruptcy is prominent because of unprecedented losses and because it was caused by a highly leveraged derivatives strategy rather than a shortage of tax revenues and excess spending. We find contagion in the bond market with significantly negative abnormal returns for municipal bond funds without direct exposure to Orange County and for non-Orange County municipal bonds. In addition, our findings suggest the contagion spills over to the common stocks of investment and commercial banks that deal in or use derivatives; however, the equities of banks unexposed to derivatives are not affected. © 2004 Blackwell Publishing Ltd.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-297-207-159-99X tex.type: [object Object]
Keywords: Bank equity; Contagion; Derivatives; Fixed income; G2/H3/K2; Municipal financing; dept.eco; dept.fin

Currency substitution: evidence from latin america - Prock, Jerry; Soydemir, Gokce; Abugri, Benjamin A (Journal of Policy Modeling, 2003)
Currency substitution represents a shift from domestic currency to foreign currency and is often related to times of high and variable inflation. In this paper, we investigate the extent of currency substitution in Argentina, Brazil and Mexico using a vector error correction (VEC) model. We empirically test this hypothesis by introducing artificial shocks to the system of equations and find that M1 response to a one standard deviation increase in that country's interest rate is negative and significant for Argentina and Brazil but not for Mexico. An artificially introduced one standard deviation increase in nominal exchange rate results in a statistically significant increase in M1 in Argentina and Brazil but again not for Mexico. Based on the patterns of the impulse response functions (IRFs) and the magnitude of the coefficients, we conclude that currency substitution occurs to a greater extent in Argentina and Brazil than Mexico. This is reflective of the implementation of relatively more credible macroeconomic policies in Mexico after the December 1994 crisis. Thus from a policymaking perspective, it is important to consider that the greater the degree of currency substitution, the more sensitive a country's monetary aggregates are to sudden movements in exchange rates, productivity and interest rates. (C) 2003 Society for Policy Modeling. Published by Elsevier Science Inc. All rights reserved.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-197-685-637-781 tex.type: [object Object]
Keywords: Currency; Latin America; Substitution; VEC; dept.eco; dept.fin

Book Review: Birthquake: the baby boom and its aftershocks. by diane j. macunovich. chicago: the university of chicago press, 2002. pp xiii, 314. 37.50 - Mills, Judith Woerner (The Journal of Economic History, 2003)
0 citations (Crossref) [2023-10-31]
Keywords: book.review; dept.eco; dept.fin

Stability of the money demand function: evidence from Ghana - Andoh, SK; Chappell, D (Applied Economics Letters, 2002)
This paper estimates the demand for money (M2) in Ghana for the period 1960 to 1996. The hypothesis is that the different macroeconomic adjustment policies (privatization, removal of foreign exchange controls etc.) which began in the mid 1980s would alter the demand for money function. The results of the study clearly show a structural break in the demand for money function in 1983.
7 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000179400600008
Keywords: dept.eco; dept.fin; peer-reviewed

In-class simulations of the iterated prisoner's dilemma game - Bodo, Peter (Journal of Economic Education, 2002)
The author developed a simple computer program for the in-class simulation of the repeated prisoner's dilemma game with student-designed strategies. He describes the basic features of the software and presents two examples for the use of the program in teaching the problems of cooperation among profit-maximizing agents.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-763-823-999-033 tex.type: [object Object]
Keywords: Computer simulation; Experiments; Prisoner's dilemma; Repeated games; dept.eco; dept.fin

Market efficiency and non-linear dependence in the Czech crown/US dollar foreign exchange market - Chappell, David; Eldridge, Robert M (Discussiones Mathematicae Probability and Statistics, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/055-245-340-128-109 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Exchange rate adjustment in partially liberalized economy - Grubacic, Sanja (Economics of Planning, 2002)
This paper develops a model of exchange rate determination in partially liberalized post-socialist economy that operates under soft budget constraints in nontradable sectors. The model captures the factors that determine the evolution of a country's external balance during the initial phase of economic liberalization. Three types of disturbances are the center of analysis: liberalization of trade and foreign exchange regime, devaluation, and price liberalization. We show that the real exchange rate appreciation may either improve or worsen the trade balance depending on the sources of this appreciation. Thus, we argue that the real exchange rate cannot reflect true country's competitiveness unless all sectors are equally exposed to hard budget constraints. The model implications are further analyzed through the empirical evidence on the relationship between the real exchange rate and trade balance in three selected East European countries.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/112-769-447-810-08X tex.type: [object Object]
Keywords: Europe; Exchange rate; External balance; Liberalization; Post-socialist economy; Soft budget constraint; balance of trade; competitiveness; dept.eco; dept.fin; exchange rate; external balance; liberalization; post-socialist economy; real exchange rate; soft budget constraint

Soft-landing monetary policy, composite leading economic indicators, and predicting the 2001 recession - Mostaghimi, Mehdi (Social Science Research Network, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/058-772-714-523-044 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Corporate groups, capital investments and stock returns in japan - Wei, Kuochiang; Xie, Feixue; Titman, Sheridan (APFA/PACAP/FMA International Finance Conference in Tokyo, Japan, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/125-992-973-641-232
Keywords: dept.eco; dept.fin

Information collection strategic design in experts-assisted decision making paradigm - Mostaghimi, Mehdi (Group Decision and Negotiation, 2001)
In an experts-assisted decision making paradigm, the information collection design becomes a strategic variable under a weak assumption that the final decision is dependent on the design used to collect information as well. As a result, the same information of the experts and the decision maker about the problem can potentially produce different final decisions for different information collection designs. The implication is that a decision maker can strategically select a design which serves his/her objective. This paper uses a Bayesian estimation methodology for combining experts' information with the decision maker's prior. An information collection process is designed by setting constraints on this model. Several designs are developed here using such controlled factors as a one-stage versus a two-stage decision process, experts' rank ordering, and group versus individual lobbying/consultation. An example is provided to illustrate the applicability of the concept. It is shown that the information produced in the process of producing a decision can also give insights into the impacts of the decision maker and the experts on the decision.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/000-610-576-094-870 tex.type: [object Object]
Keywords: Bayesian method; Experts-assisted decision making; Information theory; Reaching a consensus; dept.eco; dept.fin; experts-assisted decision making; information theory; reaching a consensus

Econometric analysis of foreign reserves and some macroeconomic variables in Nigeria (1970–2007) - Olokoyo, Felicia O; Osabuohien, Evans; Salami, O Adeleke (African Development Review, 2009)
P¿Countries are showing interest in accumulating foreign reserves to ensure macroeconomic stability. There has been some debate whether to beef up the level of nations' foreign reserves or make it lower, especially in developing countries like Nigeria. Whereas some argue that the foreign reserve determines the country's rating in the global market, others hold opposing views. In this light, this paper examined the interactive influence of foreign reserve (FRS) on some macroeconomic variables such as: economic size (GDP); trade; level of capital inflows (KFL); exchange rate (EXR); and inflation. Analyzing secondary data from CBN statistical bulletins (1970-2007), the econometric results obtained from cointegration test, vector error correction (VEC) within the framework of autoregressive distributed lags (ARDL) revealed the following: (1) existence of a long-run relationship between the variables and two cointegrating equations; (2) possibility of convergence of the variables from the short run to the long run with slow speed of adjustment. It is thus the conclusion of this paper that accumulation of large foreign reserves is not very productive in Nigeria due to its inability to induce some of the macroeconomic variables.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-248-861-812-930 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Testing Trade-Off and Pecking Order Models Under Different Institutional Environments - Farhat, Joseph B.; Cotei, Carmen; Abugri, Benjamin A. (SSRN Electronic Journal, 2009)
In this paper, we examine the differences in information asymmetry and financing patterns and a generalized version of the trade-off theory across countries with different institutional environments. We find that firms in Civil law countries have higher information asymmetry, rely more on internally generated funds, and use more short-term debt to finance their financing deficit, relative to those in Common law countries. In both Civil law and Common law countries, factors suggested by the trade-off theory explain the financing deficit coefficient in the generalized version of the trade-off model. Overall, the generalized version of the trade-off theory provides a better explanation for the changes in capital structure relative to the pecking order theory, even in countries with higher information asymmetry.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/056-876-056-037-469
Keywords: International capital structure; dept.eco; dept.fin; pecking order theory; trade-off theory

The effects of noise and manipulation on the accuracy of collective decision rules - Bodo, Peter (Algorithmic Decision Theory, 2009)
How do noise and manipulation affect the accuracy of collective decision rules? This paper presents simulation results that measure the accuracy of ten well known collective decision rules under noise and manipulation. When noise is low these rules can be divided into accurate ("good") and inaccurate ("bad") groups. The bad rules' accuracy improves, sometimes significantly, when noise increases while the good rules' performance steadily worsens with noise. Also, when noise increases the accuracy of the good rules deteriorates at different rates. Manipulation delays the effects of noise: Accuracy improvement and deterioration due to noise emerge only at higher noise levels with manipulation than without it. In some cases at high noise levels there is only a negligible difference between the accuracy of good and bad collective decision rules. © 2009 Springer-Verlag Berlin Heidelberg.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Accuracy Improvement; Acoustic noise; Collective decision; Collective decision rules; Decision theory; Fluorine containing polymers; Game theory; High noise levels; Higher noise levels; Manipulability; Manipulability of collective decisions; Noise sensitivity; Piezoelectric actuators; Simulation result; dept.eco

Economic liberalization and conditional volatility of exchange rate in sub-saharan africa: asymmetric GARCH analysis - Nandwa, Boaz; Andoh, Samuel K. (African Development Review-Revue Africaine De Developpement, 2008)
For small open economies, an understanding of movements in the exchange rate is imperative in analyzing trade and capital flows. In addition, reliable forecasting of exchange rate volatility is important in risk-taking assessment and investment decision-making, both of which are critical to long-term growth. Using an asymmetric GARCH-type approach, this paper examines the implications of economic liberalization on the stochastic behavior of the exchange rate series in a sample of sub-Sahara African (SSA) countries over the 1970-2004 period. The results indicate that exchange rate volatility is variable, and is less volatile under fixed exchange rate regime (pre-economic liberalization) and higher under flexible regime (post-economic liberalization), that is, it is asymmetric. For most of the countries, the EGARCH and TGARCH models are robust to parameter stability and gives better forecasting performance compared to the standard GARCH model.
2 citations (Crossref) [2023-10-31] tex.eissn: 1467-8268 tex.unique-id: ISI:000261215200004
Keywords: Africa; Sub-Saharan Africa; capital flow; decision making; dept.eco; exchange rate; forecasting method; investment; modeling; parameterization; stochasticity; trade flow; trade liberalization

Empirical relationship between macroeconomic volatility and stock returns: Evidence from Latin American markets - Abugri, Benjamin A (International Review of Financial Analysis, 2008)
Emerging market stock returns have been characterized as having higher volatility than returns in the more developed markets. But previous studies give little attention to the fundamentals driving the reported levels of volatility. This paper investigates whether dynamics in key macroeconomic indicators like exchange rates, interest rates, industrial production and money supply in four Latin American countries significantly explain market returns. The MSCI world index and the U.S. 3-month T-bill yield are also included to proxy the effects of global variables. Using a six-variable vector autoregressive (VAR) model, the study finds that the global factors are consistently significant in explaining returns in all the markets. The country variables are found to impact the markets at varying significance and magnitudes. These findings may have important implications for decision-making by investors and national policymakers. © 2006 Elsevier Inc. All rights reserved.
66 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-059-421-200-229 tex.type: [object Object]
Keywords: Emerging markets; Latin America; Macroeconomic volatility; Stock returns; Vector autoregressive model; dept.eco; dept.fin

Predicting us 2001 recession, composite leading economic indicators, structural change and monetary policy - Mostaghimi, Mehdi (The Singapore Economic Review, 2006)
In an attempt to predict a peak in the US economy using a classical statistical decision methodology and a Bayesian methodology and using the 1996 revised composite leading economic indicators (CLI), it is learned that the Bayesian models have generally outperformed the classical statistical ones and, among the Bayesian models, the two using two and three consecutive CLI growth rates are superior in reliability and in accuracy. These two models, however, failed to correctly predict the 2001 recession. In investigating the reasons behind their failures, we learned that: (1) if the concurrent data for the economic structure of 1983-1999 are used for the prediction, they have also been able to predict the 2001 recession correctly, but their overall reliability is not as strong as before; (2) given the overwhelming weight of the monetary policy tools in the CLI-1996 design and the combination of the economic and political events in the year 2000, the less than expected effectiveness of the monetary policy since 2001 has contributed to this failure; and (3) a possible structural change in the US economy since 2000 has also contributed to this prediction failure. © World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/198-569-450-740-397 tex.type: [object Object]
Keywords: Bayesian analysis; Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Information theory; Monetary policy; North America; Predicting recessions; Structural change; US economy; United States; dept.eco; economic analysis; economic conditions; economic structure; monetary policy; prediction; probability; structural change